2022
DOI: 10.1002/alz.12679
|View full text |Cite
|
Sign up to set email alerts
|

Education, neighborhood environment, and cognitive decline: Findings from two prospective cohort studies of older adults in China

Abstract: IntroductionThe impacts of education on cognitive decline across different neighborhood environments (NEs) have rarely been studied.MethodsWe investigated and compared the associations between educational attainment and cognitive decline using data of 1286 participants from the Taizhou Imaging Study (TIS) and the Shanghai Aging Study (SAS).ResultsCompared with low‐educated participants, in TIS with disadvantaged NE, high‐educated participants manifested a significantly slower decline in global cognition (.062 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…We categorized environmental measures into 15 exposure types ( Supplementary Table S2 ). The most common environmental exposures were green space and/or blue space (water) (30%) [ 35 , 41 , 46 48 , 51 , 53 , 57 , 60 , 61 , 63 ], neighborhood socioeconomic status (SES) (25%) [ 30 , 31 , 33 , 37 , 42 , 44 , 52 , 54 , 55 , 62 ] and recreation/physical activity facilities (20%) ( Figure 2 ) [ 6 , 25 , 29 , 42 , 49 , 50 , 57 ]. Most studies (65%) only provided environmental exposure measures at one timepoint ( Table 1 ) [ 6 , 25 27 , 29 , 31 35 , 37 , 38 , 40 45 , 53 55 , 57 59 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…We categorized environmental measures into 15 exposure types ( Supplementary Table S2 ). The most common environmental exposures were green space and/or blue space (water) (30%) [ 35 , 41 , 46 48 , 51 , 53 , 57 , 60 , 61 , 63 ], neighborhood socioeconomic status (SES) (25%) [ 30 , 31 , 33 , 37 , 42 , 44 , 52 , 54 , 55 , 62 ] and recreation/physical activity facilities (20%) ( Figure 2 ) [ 6 , 25 , 29 , 42 , 49 , 50 , 57 ]. Most studies (65%) only provided environmental exposure measures at one timepoint ( Table 1 ) [ 6 , 25 27 , 29 , 31 35 , 37 , 38 , 40 45 , 53 55 , 57 59 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nguyen et al ’s systematic review indicated that education has the potential to act as a preventive factor against dementia ( 43 ). A study in China involving 1,286 older adult individuals supports the key role of education in maintaining cognitive health in disadvantageous settings ( 44 ). The UPDRS-III is a test used to assess motor function in patients with PD.…”
Section: Discussionmentioning
confidence: 96%
“…Further subgroup analysis revealed that cognitive decline was significantly correlated with an increase in peripheral IL‐6 but not with CRP or TNF‐α levels. In addition, the incidence of cognitive decline in articles published before 2014 was significantly higher, which may be related to fewer social activities, 44 a low level of education, 45 and a disadvantaged neighborhood environment 46 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of cognitive decline in articles published before 2014 was significantly higher, which may be related to fewer social activities, 44 a low level of education, 45 and a disadvantaged neighborhood environment. 46 The effect of CRP on cognitive function has been controversial. It has been known to directly damage cerebral brain microvascular endothelial cells (ECs) 47 and further increase the permeability of the blood-brain barrier (BBB), thus activating neuroinflammation and resulting in cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation